Research and Application of Java Auto-Configuration and Deployment Tool Based on XML Metadata - Wu Haili; Gong Renbin; Wang Congbin (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
With the on-line and acceptance of A11’s production management system, the operational work is becoming increasingly critical to managing distributed system. How to ensure system version update work fast, stable and efficient, become an urgent problem to be solved. We design and implement ConfigTool which is a auto-configuration and deployment tool based on XML metadata implemented by Java. ConfigTool realizes the automated processes of decompression, modification, compression and deployment of packages. In additon, we also study and optimize the file compresssion algotithm which is used in ConfigTool. Through ConfigTool, operational work can become simple and improving work efficiency.